Tinta SePMA - Suhana, Abdul Mutalib; Nurul Shafinaz, Ismail; Mohd Basri, Basir; Nurul Aida, Othman; Noor Fazemil, Naim (Universiti Malaysia Perlis (UniMAP), 2010)
Seminar berlangsung pada 29 - 31 Mac 2010 di Dewan Kapitol UniMAP, Kangar, Perlis.